Metabolomic and transcriptomic analyses reveal a MYB gene, CsAN1, involved in anthocyanins accumulation separation in F1 between ‘Zijuan’ (Camellia sinensis var. assamica) and ‘Fudingdabaicha’ (C. sinensis var. sinensis) tea plants - Huang, Feiyi; Duan, Jihua; Lei, Yu; Kang, Yankai; Luo, Yi; Chen, Yingyu; Ding, Ding; Li, Saijun (Frontiers in Plant Science, 2022)
‘Zijuan’ (Camellia sinensis var. assamica), a somatic mutant with purple foliage and stem selected from the Yunnan Daye cultivar, has been well developed owing to abnormal pattern of anthocyanin accumulation. However, the genetic basis for the specific accumulation of phloem glycosides is not clear. Tea plant are self-incompatible, so parents with large differences in foliage color were used for crosses to investigate the genetic mechanism of anthocyanins. In this study, ‘Zijuan’ and green foliage cultivar ‘Fudingdabaicha’ (C. sinensis var. sinensis) were first used as female and male parents, respectively, to generated F1 hybrid progenies with various anthocyanin contents. In order to decipher the genetic rules of anthocyanins accumulation, we performed widely targeted metabolic and transcriptomic profiling. The results showed that cyanidin-3-O-galactoside, delphinidin-3-O-galactoside and petunidin-3-O-galactoside were the major types of anthocyanins and factors directly led to the color variation between parents and F1 plants. Transcriptomic analyses suggested the significant upregulation of anthocyanidin synthase gene (CsANS1) and CsAN1, a MYB family gene positively regulated the expression of CsANS1, in anthocyanin-rich tea plants. Furthermore, the deletion mutation of CsAN1 was found by cloning and alignment in anthocyanin-lacking cultivars. Taking together, the function deficiency of CsAN1 is predominantly responsible for the inability of anthocyanins accumulation, and this trait is heritable in progenies through hybridization. The present study elucidated the molecular basis of leaf purple trait formation in 'zijuan' and 'Fudingdabaicha' and their F1 plants, which helps to elucidate the genetic mechanism of leaf anthocyanin accumulation regulation in tea trees, and the results provide a research reference for the selection and breeding of high anthocyanin type tea varieties.